2001
DOI: 10.1080/10473289.2001.10464375
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Evaluation of Measurement Methods for One-Hour Exposures to O3, PM25, and CO

Abstract: While researchers have linked acute (less than 12-hr) ambient O 3 , PM 2.5 , and CO concentrations to a variety of adverse health effects, few studies have characterized short-term exposures to these air pollutants, in part due to the lack of sensitive, accurate, and precise sampling technologies. In this paper, we present results from the laboratory and field evaluation of several new (or modified) samplers used in the "roll-around" system (RAS), which was developed to measure 1-hr O 3 , PM 2.5 , and CO expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…In a linear model, 30-min average DustTrak concentrations were 2.8 times TEOM concentrations, with an intercept near 0 and an R 2 of 0.93 ( n= 46 ). Although it has been documented that the TEOM loses a significant fraction of semivolatile particulate matter ( Allen et al, 1997 ), this fact cannot explain the magnitude of the difference or the similar differences documented with gravimetric methods elsewhere ( Chang et al, 2001 ). A consistent multiplicative relationship implies that indooroutdoor ratios and relative comparisons between microenvironments might not be drastically affected by the sampling bias, but that our PM 2.5 measurements may need to be modified before they could be used in personal exposure models.…”
Section: Summary Statisticsmentioning
confidence: 90%
“…In a linear model, 30-min average DustTrak concentrations were 2.8 times TEOM concentrations, with an intercept near 0 and an R 2 of 0.93 ( n= 46 ). Although it has been documented that the TEOM loses a significant fraction of semivolatile particulate matter ( Allen et al, 1997 ), this fact cannot explain the magnitude of the difference or the similar differences documented with gravimetric methods elsewhere ( Chang et al, 2001 ). A consistent multiplicative relationship implies that indooroutdoor ratios and relative comparisons between microenvironments might not be drastically affected by the sampling bias, but that our PM 2.5 measurements may need to be modified before they could be used in personal exposure models.…”
Section: Summary Statisticsmentioning
confidence: 90%
“…It should be noted that past studies have found that the DustTrak overstates ambient concentrations when not calibrated to the specific ambient particles being measured, but that the bias is a consistent multiplicative factor. For example, one study (Chang et al, 2001) determined that PM 2.5 concentrations from a DustTrak were a factor of 2.1 greater than concentrations from an integrated personal exposure monitor during the summer, with an R 2 of 0.87. Similarly, another study (Levy et al, 2002) found a factor of 2.8 difference between DustTrak and TEOM measurements, with an R 2 of 0.93.…”
Section: Methodsmentioning
confidence: 99%
“…8520 in conformity with technical requirements of the V annex of the Italian Environmental Ministry Decree 23/11/1994. Ultra-fine particulate PM 2.5 has been detected with PM 2.5 EN LVS equipment (see figure 1), according to the En 12341 regulation [4,5] and Italian Law Decree n° 60 02/04/2002; the suction air flow rate is equal to 38 litres/minute and the monitoring period range is between 12 and 24 hours.…”
Section: The Experimental Monitoring Campaignmentioning
confidence: 99%
“…For a better comprehension of the data, in bold are reported those values (coming from the mean of the results of the three monitorings) exceeding the comfort and health limits deduced from the following Italian regulations: T, UR Technical Regulation UNI 10339 CO, CO 2 Italian Ministry Decree n. 159 25/11/1994 PM 10 Italian Ministry Decree n. 159 25/11/1994 PM 2,5 Environmental Ministry Decree n. 60 02/04/2002 Using PM 10 concentration as a performance indicator of the system efficiency, is it possible to underline that 55µg/m 3 of particulates, exceeding the external value of 60µg/m 3 , are introduced by the visitors in the first room before the air curtain; only 16 µg/m 3 pass through the air curtain in the antechapel room with an abatement factor of about 71%, while almost 85% of this PM 10 (14 µg/m 3 ) pass from the antechapel into the frescoes chapel.…”
Section: The Experimental Monitoring Campaignmentioning
confidence: 99%